DAWN2 Study: Diabetes-Related Stress is Harmful for Patients and Caregivers - Vinall, Maria (MD Conference Express, 2014)
The Diabetes Attitudes Wishes and Needs 2 study [DAWN2; Peyrot M et al. Diabetes Res Clin Pract 2013], with more than 16,000 participants, has reaffirmed the need to improve the self-management of type 1 diabetes mellitus (T1DM) or type 2 diabetes mellitus (T2DM) and revealed the extent of diabetes-related distress among those with diabetes and their families. Better psychosocial and behavioral outcomes are linked to the availability of a strong social support network. This article discusses the findings and implications of DAWN2.